Termination of Committee Registered with the Secretary of State's Office - Edward Arnold Jr.:::::: (1975)
A letter sent to Daniel Tolmach form the Chief of the Elections Division of the Office of the Secretary of State discussing the dissolution of a committee on February 4, 1975.